Distribution of Plantar Pressure in Soccer Players - Hawrylak, Arletta (Int J Environ Res Public Health, 2021)
(1) Background: The aim of this study was to evaluate differences in the static and dynamic distribution of foot pressure on the ground and to investigate the relationships between body mass index (BMI) and mean variables of plantar pressure between soccer players and their non-athlete peers. (2) Methods: The study involved 18 first-division Polish soccer players and 30 non-athlete physiotherapy students. The research experiment was conducted using the FreeMed platform. Basic descriptive statistics were calculated to summarize the variables. Additionally, in the static and dynamic tests, Spearman’s rank correlations between body mass index (BMI) and plantar load were calculated. (3) Results: Statistically significant differences between groups were observed in the loading of the dominant limb. A statistically significant correlation between BMI and loading of both limbs was found in the static test and between BMI and loading of the dominant limb in the dynamic test. (4) Conclusions: The baropodometric mat used in our study helped determine the plantar pressure distribution of soccer players and their non-athlete peers. Correlation analysis revealed that BMI was only associated with the mean plantar pressure of the dominant limb in the control group. Further research on a larger group of athletes is needed to determine how much sporting activity may affect the development to modifications within feet in soccer players.